TGF-β1 Expression in Osphronemus gouramy Scale Application in Rattus novergicus Tooth Socket - Prahasanti, Chiquita; Okkinardo Arief, Anneke Paramita Adityatama, Okkinardo Arief, (Opción, 2020)
The aim of the study is to observe an enhancement of TGF-β1 expression in gourami fish-scale application in Wistar rat tooth socket. As a method, thirty-six experimental animals were randomly divided into 4 groups as 7 and 14 days’ control group and 7 and 14 days’ fish-scale group. TGF-β1 expression was analyzed under immunohistochemistry on days 7 and 14. Results: Statistic test one-way ANOVA with a significant number 0.000 (p < 0,05) and Tukey HSD multiple comparisons showed a significant difference between groups. In conclusion, a Fish-scale scaffold derived from gourami can enhance the expression of TGF-β1